Descentralização administrativa: o caso da coordenação regional de polícia técnica do planalto - BA - Mendes, Maurício dos Santos (2012)
Technical Police Department (DPT) is a Bahia State Public Safety Department agency (SSP/BA), which aims to manage the services in the field of technical scientific police, promoting studies and performing surveys and other procedures, aiming at the expert evidence. DPT has several Regi onal Coordination Centers that are supported by six Bigger Regional Coordination C enters throughout the State. These Bigger Regional Coordination Centers were cre ated to manage a growing demand for expert work through internalization proc ess of Technical Police by Bahia municipalities. The objective of this exploratory s tudy was demonstrating how the administrative decentralization process took place in the Technical Police Regional Coordination Center in Planalto-BA. Thus, we adopte d the procedures of a literature search to ascertain the various concepts of central ization, decentralization, concentration and deconcentration in order to enabl e the main aspects analysis and the administrative decentralization relevance in pu blic administration. By systematic observation, it was described the operation of the Bigger Regional Coordination Center of Planalto-BA and it has been applied semis tructured interview and closed structured questionnaire techniques to listen to th e managers of the Coordination Centers linked to the Bigger Regional Coordination Center of Planalto, among them its Coordinator and DPT directors. Experts who work in the involved Coordination Centers were also interviewed in order to collect d ata that made possible to identify, among administrative activities undertaken by the C oordination, those which have decentralization characteristics. In the end of the study it was possible to conclude that DPT has not still reached the decentralization it aims since 2004, a process that has begun with the Regional Coordination Centers ex pansion in countryside. Field survey revealed various orders shortages that resul t in incomplete and inefficient works without the celerity justice requires. All th is points to the urgency in preparing a comprehensive study that would result in a proposal for procedural and structural standards which could make effective DPT decentrali zation.